MODERNISASI PENDIDIKAN DI PONDOK PESANTREN: Studi Tentang Pemanfaatan Sistem Aplikasi Pedatren dalam Meningkatkan Mutu Layanan Pondok Pesantren - Hasan Baharun; Moh Tohet; Juhji Juhji; Adi Wibowo; Siti Zainab (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2021)
This study aims to analyze and understand the use of the pedatren application system as a response to the modernization of the Nurul Jadid Islamic boarding school, Paiton, Probolinggo in improving the quality of its services. This research uses a qualitative approach with case study. This research uses a qualitative approach to the type of case study. The data collection technique is done through observation, interview, and documentation. Data analysis begins with data presentation, data reduction and ends with concluding. The results showed that the Pedatren application system was able to answer the challenges of modernizing Islamic boarding schools and the complexity of community demands during competition between educational institutions, through the provision of services regarding the identity of the students, the number of students, the development of the students' learning process, santri licensing system and payments made digitally through a virtual account.